2018
DOI: 10.1111/apt.14629
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: combination treatment of regimens based on pegylated interferon for chronic hepatitis B focusing on hepatitis B surface antigen clearance

Abstract: The "nucleos(t)ide analogues-experienced" strategy was more effective than the "De novo" strategy in achieving HBsAg loss for CHB patients. Combination treatment using regimens based on Peg-IFN may be useful to help nucleos(t)ide analogues-treated patients, who have experienced at least 48 weeks of nucleot(s)ide analogue, achieve HBsAg seroclearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 52 publications
1
38
1
2
Order By: Relevance
“…Consequently, there is some discrepancy between whether combination therapy is really more efficacious than IFN monotherapy. The discrepancy between our findings and those of Qiu et al 8 is due to the differences in selection of studies. We only selected RCTs that compared combination therapy to NA monotherapy while Qiu et al selected combination therapy without any requirement for a control group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Consequently, there is some discrepancy between whether combination therapy is really more efficacious than IFN monotherapy. The discrepancy between our findings and those of Qiu et al 8 is due to the differences in selection of studies. We only selected RCTs that compared combination therapy to NA monotherapy while Qiu et al selected combination therapy without any requirement for a control group.…”
Section: Discussioncontrasting
confidence: 99%
“…In an era where there is increasing interest in functional cure defined as HBsAg loss, accurate estimates of the relative efficacy of current therapies are much needed. In a recent meta‐analyses, Qiu et al 8 examined combination therapies based on pegylated IFN and its impact on HBsAg clearance. The authors found that the de novo peginterferon and NA strategy led to HBsAg loss of 9%(95% CI 6%, 10%), add‐on strategy 8% (95% CI 5%, 13%) and switch strategy 14% (95% CI 9%, 20%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an uncertain or even lifelong period of NUC treatment may be needed for most patients with chronic HBV infection. Alternatively, PEG-IFN-α treatment can lead to HB e-antigen (HBeAg) clearance and HBsAg seroconversion in 10-30% of cases within a definite duration of therapy (6,9,10). Beside direct antiviral effects, the immunomodulatory property of IFN-α may ultimately induce an immune control of HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Current approaches include de novo dual therapy in NA‐naïve CHB, or extension to PegIFN as “add‐on” or “switch‐to” therapy in “NA‐experienced” patients. Focusing on HBsAg clearance, Qiu et al performed a systematic review with meta‐analysis to evaluate combination therapy with NAs and PegIFN for CHB . The authors identified 24 studies that met inclusion criteria.…”
mentioning
confidence: 99%